Risk Factors Affecting the Death of Hospitalized Patients with COVID-19 in the South of Iran - Ehsan Goroei Sardu; Fatemeh Rezabeigi Davarani; Bahareh Kermani; Reza Faryabi; Shiva Kargar; Shamim Tashakori; Salman Daneshi (Shahid Sadoughi University of Medical Sciences, 2023)
Background: Identifying effective factors in death caused by the infection of COVID-19 is one of the most worrisome issues in the globe. This study aims to investigate the frequency of risk factors leading to death in patients with COVID-19. Methods: This was a retrospective descriptive study done on 150 confirmed cases of  COVID-19 in Imam Khomeini Hospital in Jiroft in 2019. Patients were included in the study by census method. The required information was extracted and recorded in the researcher's checklist; which included demographic and social characteristics of patients (age, gender, smoking, and opium consumption), underlying disease,test results (leukopenia, leukocytosis, neutropenia, decrease in albumin, increase in creatinine, ALT, AST, LDH and CRP), and the RT-PCR test.,. The researchers analyzed data using independent sample t-test, and chi-square by SPSS-V22.  Results: The mean age of the patients was 72.19 ± 15.97. Most of those who died with COVID-19 were men. There was a statistically significant relationship between the use of drugs and the death of patients with COVID-19(P-value<0.05). The average body mass index (BMI) of the confirmed patients was 31.14 ± 7.08 kg/m2 in the overweight group (P-value<0.001). Moreover, there was a significant relationship between the risk factors CRP, ALB, AST, ALT, Cr, lym, Neut, WBC and inevitable death in patients with COVID-19(P-Value<0.001). Regarding underlying diseases, diabetes, lung, and kidney diseases have been observed in most terminal patients (P-value<0.001). Conclusion: Old age, male gender, high BMI, blood pressure, increased factors of CRP, AST, ALT, Cr, lym, Neut, WBC, and decreased ALB are among the risk factors leading to death in COVID-19 patients.